Implementation of the Kahoot Application on Students’ Learning Motivation in Learning in Class 6 of SDN 7 Matajang, Bulukumba District - Andi Muhammad Barkah Ambarsyah; Jumriani Jumriani; Muhajir Muhajir (Edumaspul: Jurnal Pendidikan, 2024)
In the world of education, learning media is very necessary in an effort to increase students' understanding, knowledge and absorption of certain learning content so that the learning process becomes more interesting and optimal. This learning media is an important element in the learning process, so that students can more easily understand the content of the material presented by the teacher and increase student interest and motivation in learning. One learning media that can be used to motivate students to learn is the implementation of education-based digital learning media, including the implementation of the Kahoot application learning media. The purpose of this research is to determine the implementation of the Kahoot application to increase student learning motivation. The method used is qualitative research with an experimental research approach and field research using topics and research objects from grade 6 students at SDN 7 Matajang Bulukumba. The results of the research show that by implementing the Kahoot application as a learning medium, the interest and learning motivation of grade 6 students at SDN 7 Matajang Bulukumba increases and achieves the expected learning outcomes.